2017
DOI: 10.1007/s11695-017-3008-8
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Alcohol Use and Associated Characteristics Following Bariatric Surgery

Abstract: Findings have implications for pre- and postoperative prevention and intervention efforts. Additional research is needed to further elucidate risk factors for problematic alcohol use following bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
0
14
0
2
Order By: Relevance
“…Post-operative alcohol use has been identified as a predictor for weight regain [27]. Furthermore, psychiatric comorbidities, like prior depression, have been reported to be high among patients with hazardous alcohol consumption after gastric bypass surgery [35]. The present study population mentioned psychiatric comorbidities, as well as altered effects of alcohol, as drivers of increased alcohol use.…”
Section: Discussionmentioning
confidence: 63%
“…Post-operative alcohol use has been identified as a predictor for weight regain [27]. Furthermore, psychiatric comorbidities, like prior depression, have been reported to be high among patients with hazardous alcohol consumption after gastric bypass surgery [35]. The present study population mentioned psychiatric comorbidities, as well as altered effects of alcohol, as drivers of increased alcohol use.…”
Section: Discussionmentioning
confidence: 63%
“…Use of the data allowed the evaluation of changes in documented alcohol use from 2 years before to 8 years after the surgical procedure, building on past US prospective cohort studies. 7 , 13 , 14 , 15 , 16 , 17 , 38 , 39 Second, this study is the first, to our knowledge, to evaluate alcohol-related outcomes of bariatric surgical procedures in a predominantly male population.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] To date, most research on alcohol-related risks after a bariatric surgical procedure has been limited to laboratory studies [11][12][13] and uncontrolled cohort studies. 7,[13][14][15][16] The only studies that included nonsurgical control patients suggested that Roux-en-Y gastric bypass (RYGB) was associated with increased alcohol use, unhealthy alcohol use, and alcohol use disorder. 15,17 However, these studies in Swedish populations did not include the most common bariatric surgical procedure performed in the US, laparoscopic sleeve gastrectomy (LSG).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that one unit of alcohol will result in higher blood alcohol levels after RYGB, the relative weight on the response alternatives to these questions may be underestimated after surgery. Several studies have applied AUDIT on patients after bariatric surgery (2,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…This applies to two of the questions in the AUDIT: “How many drinks containing alcohol do you have on a typical day when you are drinking?” and “How often do you have six or more drinks on one occasion?” Considering that one unit of alcohol will result in higher blood alcohol levels after RYGB, the relative weight on the response alternatives to these questions may be underestimated after surgery. Several studies have applied AUDIT on patients after bariatric surgery ( 2 , 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%